Exploring resistive switching‐based memristors in the charge–flux domain: A modeling approach. (7th November 2017) - Al Chawa, M. Moner; Picos, Rodrigo; Roldan, Juan B.; Jimenez‐Molinos, Francisco; Villena, Marco Antonio; de Benito, Carol
Summary: We analyzed resistive switching‐based memristors by using the charge–flux relations instead of the traditional current–voltage approach. We employed simulated and experimental data to develop a model that can be easily included in circuit simulators. Physical simulations of devices with different conductive filament sizes were employed to fit the 3‐parameter model introduced. Later on, the relations between the model parameters and the conductive filament geometrical features were characterized in‐depth. In addition, a model to obtain the energy employed in the reset process was presented. Finally, we used the model to estimate the experimental conductive filament radius distribution using a set of 3000 reset cycles. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : In this paper, we analyze resistive switching‐based memristors using charge–flux relations instead of the traditional current–voltage approach. We employed simulated and experimental data to develop a model that can be easily included in circuit simulators. Agreement between the model and experimental results is excellent, as can be seen in the figures.